The Effect of Shopee Live Content Marketing on Customer Retention with Customer Engagement as an Intervening Variable of Shopee Live Users on the Shopee Application in Padang City - Nurul Ayundah Putri; Whyosi Septrizola (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The purpose of this study is to analyze: (1) The effect of content marketing on customer retention of Shopee Live users on the Shopee application in Padang City, (2) The effect of content marketing on the customer engagement of Shopee Live users on the Shopee application in Padang City, (3) The effect of customer retention on customer engagement of Shopee Live users on the Shopee application in Padang City, and (4) The effect of content marketing on customer retention through customer engagement as intervening variables of Shopee Live users on the Shopee application in Padang City.This study is a quantitative descriptive research. The sample size in this study was 200 respondents using purposive sampling techniques. Data analysis method using PLS-SEM analysis using Smart PLS 4. The results of the study are: (1) Content marketing has a significant effect on customer retention of Shopee Live users on the Shopee application in Padang City, (2) Content marketing has a significant effect on customer engagement of Shopee Live users on the Shopee application in Padang City, (3) Customer engagement has a significant effect on customer retention of Shopee Live users on the Shopee application in Padang City, and (4) Content marketing has a significant effect on customer retention through customer engagement as an intervening variable for Shopee Live users in the Shopee application in Padang City.